HIGHER EDUCATION AND GLOBAL COMPETENCE: RENEWING THE EDUCATIONAL CONCEPT OF UNIVERSITIES IN RUSSIA - Polukhina, Marina; Doskovskaya, Maria (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The world is changing at an increasing pace. We are living in a time of dramatic transformations such as globalization with its impact on economic competitiveness and social cohesion, international mobility, new occupations and careers, advances in technology and its use. Such processes affected the higher education of many countries, including Russia, and created the concept of global education. Nowadays our students have the opportunity and challenge of living and working in such a diverse and rapidly changing world. Thus, renewing the educational concept of universities is becoming relevant. In this article, the authors consider definitions and dimensions of global competence as an essential component of training young specialists as well as 21st century learning in the context of global competence. The authors present how global competence is defined as the combination of the four dimensions and how each dimension builds on specific knowledge, skills, attitudes and values: Also, the paper considers the ways of renewing higher education in Russia and points of growth.